2008
DOI: 10.1002/jssc.200700380
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonication followed by single‐drop microextraction combined with GC/MS for rapid determination of organochlorine pesticides from fish

Abstract: A novel, rapid and simple sample pretreatment technique termed ultrasonication followed by single-drop micro-extraction (U-SDME) has been developed and combined with GC/MS for the determination of organochlorine pesticides (OCPs) in fish. In the present work, the lengthy procedures generally used in the conventional methods like, Soxhlet extraction, supercritical fluid extraction, pressurized liquid extraction and microwave assisted solvent extraction for extraction of OCPs from fish tissues are minimized by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(19 citation statements)
references
References 31 publications
1
18
0
Order By: Relevance
“…Ye et al [27] also reported similar observation and recommended that HA concentration must be less than 50 mg/L. Shrivas and Wu [29] described ultrasonication followed by SDME combined with GC-MS for rapid determination of OCPs in fish sample. They analyzed OCPs from fish tissue by spiking 1.0 g of fish tissue followed by ultrasonication with water-miscible solvents.…”
Section: Sdme With Gc-msmentioning
confidence: 68%
“…Ye et al [27] also reported similar observation and recommended that HA concentration must be less than 50 mg/L. Shrivas and Wu [29] described ultrasonication followed by SDME combined with GC-MS for rapid determination of OCPs in fish sample. They analyzed OCPs from fish tissue by spiking 1.0 g of fish tissue followed by ultrasonication with water-miscible solvents.…”
Section: Sdme With Gc-msmentioning
confidence: 68%
“…As in the previous results, this supports the notion that the polar features could be very similar to PCBs found in fish tissue. [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] Moreover, the ice-cold condition was strongly suggested to remove the heat disturbance.…”
Section: Resultsmentioning
confidence: 99%
“…4,[12][13][14][15] In addition, GPC, ASE, soxhlet, ultrasonic extraction and single-drop were also used to promote extraction efficiency from fish several years ago. 4,10,14,[16][17][18][19] Moreover, researchers have focused on simplified and rapid determination of PCBs, such as by using screening, programmable temperature vaporization-large volume injection (PTV-LVI) or high throughput methods. Most literature have focused on six PCBs (IUPAC Nos.…”
Section: -11mentioning
confidence: 99%
“…Different organic solvents, namely toluene, iso-octane, chloroform and n-hexane, are frequently used in SDME, as the acceptor phase, of liquid drop to extract the pesticides from aqueous solution [3,39]. After three replicate analysis, the chromatographic signals obtained from the analytes using nhexane as the acceptor phase, are approximately two times higher than the signals obtained with dichloromethane and tetrachloromethane.…”
Section: Solvent Selectionmentioning
confidence: 99%
“…Ahmadi et al employed some modification of the needle tip, causing its cross section to increase and increasing adhesion force between the needle tip and the drop, thereby increasing drop stability and achieving a higher stirrer speed (up to 1,700 rpm) [30]. SDME in pesticide residues analysis has been applied with success in both liquid water [27,30,31], juices [32,33], wine [34,35], oils [36] and solid samples (vegetables [24,37,38], fish [39] by providing low limits of detection and high selectivity as compared with classic robust sample preparation techniques. The novel approachs of SDME were developed by different authors.…”
Section: Introductionmentioning
confidence: 99%